PEMBERDAYAAN KADER GERBANGMAS MELALUI PELATIHAN PEMBUATAN MPASI PAK OLAN DI DESA KALIBOTO KIDUL KECAMATAN JATIROTO KABUPATEN LUMAJANG DENGAN PENDEKATAN COMMUNITY-BASED RESEARCH (CBR) - Nur Khasanah; Ahmad Sahal Aqil Abrori; Agung Setyo Wibowo; Muhammad Boy Muslim; Ferdy Pratama; Funsu Andiarna (Jurnal Abdimas Bina Bangsa, 2022)
This community service aims to improve the nutritional status in 6 to 24-months-old children by PAK OLAN Breastfeeding Food (MPASI) program. Using Community-Based Research (CBR) method, the service team are accompanied by Gerbangmas cadre and local community to participate in making plans or arrangements, organizing an event, and evaluating the results of the community service. The results indicate that the success of MPASI program is determined by the level of Gerbangmas cadre participation in implementing and sustaining the program. This is indicated by awareness of parents about nutrition improvement through MPASI and innovative ideas of MPASI by Gerbangmas cadre such as PAK OLAN MPASI that children like